Women as Heads of Families: An Analysis of Musdah Mulia's Thoughts and Interpretation Methods on Women's Leadership - Nuraeni, Ani; Ariyanto, M. Agni (CV. Strata Persada Academia, 2025)
The discourse on women’s leadership in the family has gained increasing scholarly attention, particularly in the context of gender equality and social transformation. In patriarchal societies, the role of family head has traditionally been ascribed to men, often marginalizing women’s contributions. However, as Musdah Mulia exemplifies, modern Islamic thought challenges these conventional gender roles. This study analyzes Musdah Mulia’s thoughts and interpretative methods regarding women as heads of families. Through a hermeneutic-contextual approach and thematic interpretation (tafsir maudhu’i), Musdah Mulia argues that the concept of qiwāmah in QS. Al-Nisa: 34 should be understood as a flexible, context-dependent construct rather than an absolute principle of male superiority. Her reinterpretation highlights the necessity of education, economic access, and shared responsibility within family leadership. The findings suggest that Musdah Mulia’s reinterpretation of women’s leadership as heads of families contributes to a more egalitarian understanding of gender roles, challenging patriarchal norms and advocating for policy changes supporting women’s empowerment. However, resistance from traditionalist perspectives and cultural biases remains a significant obstacle. This study recommends further research on the practical implications of Musdah Mulia’s reinterpretation, particularly in legal and policy frameworks related to Islamic family law.